Avaliação de Interfaces de Usuário voltada à Acessibilidade em Dispositivos Móveis: Boas práticas para experiência de usuário - Guimarães, Ana Paula Nunes; Tavares, Tatiana Aires (Anais Estendidos do Simpósio Brasileiro de Sistemas Multimídia e Web (WebMedia), 2014)
The use of mobile devices brings great benefits of connectivity to its users. However, access to information through these devices is a new challenge of interaction for users who have some kind of disability. Currently, most mobile applications have accessibility barriers that make it difficult or impossible the usage for many individuals with special needs. To ensure access to the content to all users regardless of their health status, this paper proposes a model for evaluating user interfaces accessibility focused on mobile devices. The proposed model takes into account the users experience without neglecting the specificities of mobile context and accessibility scenario. As partial results, there is a group of perceptions observed from tests at evaluating a mobile application developed for the deaf. Results show the challenges and new perspectives to evaluate the mobile accessibility, since few methods consider these two contexts.